Minimum Age of Criminal Liability of Children - Kočivnik, Maša; Šepec, Miha (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges: Exploring Opportunities and Challenges, 2025)
Accusing the perpetrator of criminal responsibility makes sense only if he understands the significance of his actions. Since it is a generally accepted fact that children are not capable of developing culpable responsibility until a certain age, practically every criminal law in the world sets an age limit up to which criminal responsibility cannot be attributed to a child. Until a certain age, the child is not mentally developed and mature enough to be able to understand the consequences of his behaviour, and thereby, he develops guilt in the criminal law sense, which deserves the criminal law repression of the state. The question remains, what should be the age up to which the child does not answer for committing a crime? In this chapter, the authors examine this question. At the same time, we wonder whether it is fair and just that a child who commits a serious crime, while being aware that his behaviour is evil (so he actually understands the consequences of his action), is not criminally responsible just because he has not yet reached the objectively set age in the Criminal Code.